THE IMPLEMENTATION OF C-ID, R2D2 MODEL ON LEARNING READING COMPREHENSION - yudi hari Rayanto (EDUCAFL : Journal of Education of English as Foreign Language, 2018)
ABSTRACT:The purposes of this research are to find out, 1) whether C-ID, R2D2 model is effective to be implemented on learning Reading comprehension, (2) college students’ activity during the implementation of C-ID, R2D2 model on learning Reading comprehension, and 3) college students’ learning achievement during the implementation of C-ID, R2D2 model on learning Reading comprehension. All data are gained from observation sheets from two observers and test given to 31 college students. All data are analyzed by using descriptive quantitative study. The result shows thatC-ID, R2D2 model is effective to be implemented. It can be seen from the result of observation that 3,96 which can be called as high category level. In college students’ activity during its implementation is high, that is 3,97, and also from the total result of college student’s learning achievement, all students get score more than 90.Key words: C-ID, R2D2, Learning, Reading comprehension